Comparison of Students' Learning Behaviors in Face-to-Face and Online Lectures (Case Study: 2019 Cohort Students of Japanese Studies Program, Universitas Airlangga) - Syahrial, Ghulam Bintang (Riwayat: Educational Journal of History and Humanities, 2025)
This article discusses the phenomenon of online learning, which has been accelerated by the COVID-19 pandemic. The pandemic has compelled various sectors, including education, to adapt. In higher education, Japanese language learning has inevitably been conducted online. The sudden acceleration due to the pandemic has inevitably led to changes in students' learning methods. This article investigates how students of the Japanese Studies Program at Airlangga University, particularly the 2019 cohort, adapt to new learning habits from the perspective of technological determinism by Marshall McLuhan. The study employs a qualitative method, conducting interviews with five students. The results reveal that changes in teaching methods by Japanese language course instructors triggered changes in students' learning approaches. These adjustments aimed to facilitate the teaching-learning process in an online setting. However, online learning posed challenges such as distractions, fatigue, and the absence of direct discussion with peers. To overcome these obstacles, students adopted alternative strategies to understand Japanese grammar patterns.